2017
DOI: 10.3892/mmr.2017.7612
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits proliferation and migration through SIRT1 mediated post-translational modification of PI3K/AKT signaling in hepatocellular carcinoma cells

Abstract: Resveratrol (RES), a polyphenolic compound present in grapes and red wine, has potential anticancer properties. The present study aimed to examine the effects of resveratrol and its underlying mechanism on hepatocellular carcinoma (HCC) cell lines HepG2, Bel-7402 and SMMC-7721. It was demonstrated that resveratrol inhibited the viability and proliferation of HCC cells assessed by MTT and EdU assays. TUNEL assay revealed that resveratrol induced cell apoptosis by increasing HCC apoptosis rate from 3±0.78% to 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 39 publications
(49 reference statements)
5
67
0
Order By: Relevance
“…Based on this, we detected that RES downregulated the expression of β‐catenin time‐ and dose‐dependently in MCF7/ADR cells. RES is a well‐known activator of SIRT1 which was reported to inhibit proliferation and migration through SIRT1‐mediated posttranslational modification of PI3K/Akt signaling in hepatocellular carcinoma cells . Another report revealed that SIRT1 promotes EMT in colorectal cancer by regulating Fra‐1 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, we detected that RES downregulated the expression of β‐catenin time‐ and dose‐dependently in MCF7/ADR cells. RES is a well‐known activator of SIRT1 which was reported to inhibit proliferation and migration through SIRT1‐mediated posttranslational modification of PI3K/Akt signaling in hepatocellular carcinoma cells . Another report revealed that SIRT1 promotes EMT in colorectal cancer by regulating Fra‐1 .…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/AKT pathway is a vital regulator in cell proliferation, metastasis and apoptosis by modulating downstream targets, such as mammalian target of rapamycin (mTOR) and Cyclin-dependent kinase inhibitors (27). Increasing evidence shows that PI3K/AKT pathway is closely related with the tumorigenesis, such as breast cancer (28), hepatocellular carcinoma (29) and PC (30). Dysregulated expression of PIK3CA led to abnormal activation of PI3K/AKP pathway and consequently development of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol (Res) is a natural phenolic compound whose anti‐inflammatory, anticancer, and antioxidant effects have been confirmed by the medical community . According to the literature reports, Michael acceptors can react with cysteine thiolate (soft base) groups in Kelch‐like ECH–related protein 1 (Keap1) and consequently induce nuclear factor erythroid 2–related factor 2 (Nrf2) accumulation that leads to upregulated expression of antioxidant responsive element (ARE)‐mediated antioxidative and cytoprotective enzymes.…”
Section: Introductionmentioning
confidence: 99%